PENGEMBANGAN SISTEM PAKAR PERENCANAAN KARIER SISWA DENGAN METODE FORWARD CHAINING DI SMK NEGERI 2 PADANG PANJANG - Rifdian, Bayu Rahmat; Anggraini Samudra, Ami; Hendra, Herisvan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Career planning is an important aspect of vocational education to prepare students for the workforce. At SMKN 2 Padang Panjang, career guidance is still conducted manually using conventional questionnaires, which is considered inefficient, especially given the limited number of guidance and counseling (BK) teachers. This research aims to develop a web-based expert system for career planning using the forward chaining method to provide career recommendations tailored to students' interests and talents. The study employs the Research and Development (R&D) model and an Agile-based SDLC software development methodology. The system is built using the Laravel framework and tested through alpha testing and beta testing involving experts and end-users. The test results demonstrate that the system can provide relevant career recommendations, accelerate the guidance process, and improve the accuracy and efficiency of counseling services, with a system validity of 97.96%, practicality validity of 93.85%, and validation by field respondents of 96.67%. This system also assists BK teachers in managing student data and reducing administrative workloads. In conclusion, the development of this expert system contributes to the digitization of career guidance services in vocational schools and serves as an effective and adaptive alternative solution to meet students' needs in the digital era.